Factors Affecting Cheating Behavior among Accounting Students (Using the Theory of Planned Behavior) - Muhannad Atmeh; Husam Al-Khadash (Journal of Accounting, Business and Management (JABM), 2008)
As cheating behavior by accounting students may indicate to future unethical professional behavior, the purpose of this study is to examine students motivations (intentions) and abilities toward cheating behavior relying on the theory of planned behavior. It aims to analyze factors that might affect cheating among accounting students. Data were collected from the accounting students at the Hashemite University in Jordan, which is a large sized public university in the Zarqa Governance. A total of 307 accounting students participated in the study. Regression analysis was used to analyze the data and descriptive statistics were employed to summarize the information. Findings suggest that females, students with a high GPA and last-year students may be less likely to cheat. Also the results indicate that there are significant relationships between deterrents, alienation and neutralization with prior cheating and cheating likelihood.